Corporate Culture - Externally Committed Values: The Case Study of a Technology and Telecommunications Enterprise Listed on The Vietnam Stock Market - Duyen, Chau Thi Le; Anh, Nguyen Pham Tuyet; Phat, Le Trung Ngoc; Thuong, Duong Thi Be (International Journal of Membrane Science and Technology, 2023)
This study investigates the external endorsement of corporate cultural values based on Martin and Frost’s (1988) model. The research findings reveal that FPT Corporation significantly emphasizes Humanism, Financial, and Product values in its business activities over the three years T-T+2. The corporate culture contributes a vital role in fostering the growth of the organization. The study’s longitudinal evaluation demonstrates that it is appropriate that FPT spends a prime concern on Humanism since employee commitment and dedication are crucial for the company’s present success. Moreover, the high emphasis on Financial and Product values is well-founded because transparent financial reporting is essential to prevent misinterpretations and attract investment, while the quality of the products symbolizes the company’s credibility and ensures substantial revenue generation.